Influence of bacterial and alveolar cell co-culture on microbial VOC production using HS-GC/MS - Fenn, Dominic; Ahmed, Waqar M.; Lilien, Thijs A.; Kos, Renate; Tuip de Boer, Anita M.; Fowler, Stephen J.; Schultz, Marcus J.; Maitland-van der Zee, Anke H.; Brinkman, Paul; Bos, Lieuwe D. J. (Frontiers in Molecular Biosciences, 2023)
Volatile organic compounds (VOCs) found in exhaled breath continue to garner interest as an alternative diagnostic tool in pulmonary infections yet, their clinical integration remains a challenge with difficulties in translating identified biomarkers. Alterations in bacterial metabolism secondary to host nutritional availability may explain this but is often inadequately modelled in vitro. The influence of more clinically relevant nutrients on VOC production for two common respiratory pathogens was investigated. VOCs from Staphylococcus aureus (S.aureus) and Pseudomonas aeruginosa (P.aeruginosa) cultured with and without human alveolar A549 epithelial cells were analyzed using headspace extraction coupled with gas chromatography-mass spectrometry. Untargeted and targeted analyses were performed, volatile molecules identified from published data, and the differences in VOC production evaluated. Principal component analysis (PCA) could differentiate alveolar cells from either S.aureus or P.aeruginosa when cultured in isolation based on PC1 (p = 0.0017 and 0.0498, respectively). However, this separation was lost for S.aureus (p = 0.31) but not for P.aeruginosa (p = 0.028) when they were cultured with alveolar cells. S.aureus cultured with alveolar cells led to higher concentrations of two candidate biomarkers, 3-methyl-1-butanol (p = 0.001) and 3-methylbutanal (p = 0.002) when compared to S.aureus, alone. P.aeruginosa metabolism resulted in less generation of pathogen-associated VOCs when co-cultured with alveolar cells compared to culturing in isolation. VOC biomarkers previously considered indicative of bacterial presence are influenced by the local nutritional environment and this should be considered when evaluating their biochemical origin.